1982
DOI: 10.1149/1.2123849
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity, Photoconductivity, and Luminescence Studies on Some Silversulfamides

Abstract: Electrical conductivity, photoluminescence, and diffuse reflectance spectra have been measured for the following silversulfamides: O2Sfalse(normalNHAg)2 , O2Sfalse(normalNHAgfalse)false(NAg2false)·NH3·H2O , O2Sfalse(NAg2)2 , and O2Sfalse(NAg2)2·2NH3 . They have been discussed in relation to their crystal structures. With increasing silver content the conductivity increases and the absorption edges of the reflectance spectra are red shifted. The luminescence data have been attributed to centers of the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…16 Applications of Ag(I) materials include the use of silver halides as photographic materials 17 and as optical fibers in the mid-IR region, 18 and the use of silver(I) oxides as photocatalysts, 19 conductors, semiconductors, and photoconductors. 1,[20][21][22] We report herein a study of the temperature-dependent photoluminescence properties of single crystals of alkali halides doped with dicyanoargentate(I) ions. An earlier study in our laboratory has suggested the formation of luminescent exciplexes in [Ag(CN) 2 -]/KCl mixed crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Applications of Ag(I) materials include the use of silver halides as photographic materials 17 and as optical fibers in the mid-IR region, 18 and the use of silver(I) oxides as photocatalysts, 19 conductors, semiconductors, and photoconductors. 1,[20][21][22] We report herein a study of the temperature-dependent photoluminescence properties of single crystals of alkali halides doped with dicyanoargentate(I) ions. An earlier study in our laboratory has suggested the formation of luminescent exciplexes in [Ag(CN) 2 -]/KCl mixed crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Gold(I) compounds have been suggested for applications such as biosensors, photocatalysts, drugs for rheumatoid arthritis, and optical sensors for volatile organic compounds . Applications of Ag(I) materials include the use of silver halides as photographic materials and as optical fibers in the mid-IR region, and the use of silver(I) oxides as photocatalysts, conductors, semiconductors, and photoconductors. , …”
Section: Introductionmentioning
confidence: 99%
“…More recently, luminescence studies of different Ag(I) centers have been reported in glassy and crystalline borate and in phosphate glasses . Interest in silver(I) oxides has been stimulated by their use as conductors, semiconductors, and photoconductors. , …”
Section: Introductionmentioning
confidence: 99%
“…20 Interest in silver-(I) oxides has been stimulated by their use as conductors, semiconductors, and photoconductors. 6,[21][22][23] Despite the tremendous attention given to Ag(I) halides, oxides, and doped ions in the literature, very little work has been reported to address the photophysics and photochemistry of Ag(I) coordination compounds. [24][25][26][27] We have recently studied Ag(I) coordination compounds to elucidate fundamental issues in chemistry such as ligand-unsupported Ag-Ag closed-shell interactions (argentophilic attraction) 28 and inorganic excimers and exciplexes.…”
Section: Introductionmentioning
confidence: 99%